Effect of mechanical impedance on root and shoot growth of rice at time intervals - Ali, AHMZ (Dhaka University Journal of Biological Sciences, 2011)
In a phytotron chamber the effect of mechanical impedance on root and shoot growth of BR?29 variety of rice at different time intervals reaveled that length of the seminal axis and length of the longest leaf extended linearly in both unimpeded and impeded treatments. Diameter of roots increased in impeded treatment. The number of first order laterals also increased linearly with time in both unimpeded and impeded treatments. Although there were always significantly more laterals on the unimpeded root axes, lateral spacing does not show any tendency to change with time. Root growth rate was nearly half in impeded than in unimpeded treatment. The pattern of root length in unimpeded (UI) did not differ from that of the pattern in impeded (I) treatment as the ratios (I/UI) were more or less constant with time. The time of leaf appearance was delayed by one ? two days and leaf growth period was shortened by one day in impeded than in unimpeded treatment. Leaf growth rates did not differ significantly between day and night time although night time growth rates were always slightly less than day time. Key words: Mechanical impedance; Pattern of root growth; Time interval; Shoot growth; Rice DOI: http://dx.doi.org/10.3329/dujbs.v19i2.8953 DUJBS 2010; 19(2): 119-128